Differences in the determinants and targeting of anti-dumping: China and India compared - Meng, Ning; Milner, Chris; Song, Huasheng (Taylor & Francis, 2016)
Despite both being developing countries, China and India have markedly contrasting patterns in their use and targeting of antidumping (AD) measures. We explore the factors driving AD use by these two countries, considering in turn macroeconomic, strategic and other determinants. We find more regular or systematic features of AD use by China, while India displays a less systematic pattern of AD use. Economic growth, AD club effect and FTA participation are shown to constrain AD use by China. Compared to India, AD use by China is also more sensitive across industries. Furthermore, China targets developed countries more than developing countries, while India is less discriminating with respect to the country type it targets.